EVINACUMAB, A NEW TREATMENT FOR FAMILIAL HYPERCHOLESTEROLAEMIA: MECHANISM OF ACTION, SAFETY AND EFFICACY - Majchrowicz, Gabriela; Mikołaj Jońca; Kurys, Natasza; Piekarska, Weronika; Litke, Szymon (International Journal of Innovative Technologies in Social Science, 2026)
Homozygous familial hypercholesterolemia (HoFH) is a rare genetic disorder characterized by extremely elevated low-density lipoprotein cholesterol (LDL-C) levels and a markedly increased risk of premature atherosclerotic cardiovascular disease. The aim of this review was to summarize current knowledge on the pathophysiology, diagnosis, and management of HoFH, with particular emphasis on angiopoietin-like protein 3 (ANGPTL3) inhibition and the clinical role of evinacumab. A comprehensive analysis of published clinical trials, guidelines, and observational studies was conducted to evaluate available diagnostic criteria and therapeutic strategies. Standard lipid-lowering therapies often fail to achieve recommended LDL-C targets in HoFH due to impaired LDL receptor function. Evinacumab, a fully human monoclonal antibody targeting ANGPTL3, has demonstrated substantial LDL-C reductions independent of LDL receptor activity in both adult and pediatric patients. Clinical studies report LDL-C reductions of approximately 45–50%, along with a favorable safety profile. In conclusion, ANGPTL3 inhibition with evinacumab represents a significant advancement in the treatment of HoFH, offering an effective therapeutic option for patients with inadequate response to conventional lipid-lowering therapies.